2021
DOI: 10.1038/s41598-021-92206-y
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 antibodies in Saint Petersburg, Russia: a population-based study

Abstract: Properly conducted serological survey can help determine infection disease true spread. This study aims to estimate the seroprevalence of SARS-CoV-2 antibodies in Saint Petersburg, Russia accounting for non-response bias. A sample of adults was recruited with random digit dialling, interviewed and invited for anti-SARS-CoV-2 antibodies. The seroprevalence was corrected with the aid of the bivariate probit model that jointly estimated individual propensity to agree to participate in the survey and seropositivit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
1
18
2
Order By: Relevance
“…Of those who stated they had not been vaccinated and did not report having previously been ill with COVID-19, 292 (45%) were seropositive, suggesting an appreciable level of unrecognized infection. Our overall estimates of seroprevalence (crude 65%, adjusted 72.6%) is appreciably higher than found in St Petersburg in June 2020 ( 3 ) (10%) or in Chelyabinsk (25%) in September–December 2020 ( 4 ). This result is consistent with the second wave of the pandemic in Russia (peak November–December 2020) being larger than the first (peak May–June 2020); our study started during the vaccination period.…”
contrasting
confidence: 67%
See 1 more Smart Citation
“…Of those who stated they had not been vaccinated and did not report having previously been ill with COVID-19, 292 (45%) were seropositive, suggesting an appreciable level of unrecognized infection. Our overall estimates of seroprevalence (crude 65%, adjusted 72.6%) is appreciably higher than found in St Petersburg in June 2020 ( 3 ) (10%) or in Chelyabinsk (25%) in September–December 2020 ( 4 ). This result is consistent with the second wave of the pandemic in Russia (peak November–December 2020) being larger than the first (peak May–June 2020); our study started during the vaccination period.…”
contrasting
confidence: 67%
“…Few published estimates of antibody seroprevalence for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Russia exist. A St. Petersburg survey in June 2020 used random-digit dialing to contact 66,250 residents; of those, 1,038 provided a blood sample, and the samples had 9%–10% seropositivity ( 3 ). A study conducted in Chelyabinsk (September 28–December 30, 2020) recruited 1,091 high-risk workers (healthcare workers, education staff, and supermarket employees) > 18 years of age.…”
mentioning
confidence: 99%
“…19 We used CMIA Abbott and ELISA Coronapass for the first publication of a populationbased seroprevalence study in May June 2020. 6 The first round of the study analysis showed that the use of ELISA Coronapass results in a slightly higher seroprevalence estimation. This was the initial reason for the independent validation of the test performance.…”
Section: Methodsmentioning
confidence: 99%
“…Information about the corresponding seroprevalence study in St. Petersburg is available in the detailed report 6 . In brief, we obtained a representative population sample through phone by using random­digit dialing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation